Production of lipopeptide biosurfactant by Kurthia gibsonii KH2 and their synergistic action in biodecolourisation of textile wastewater - Mohd Nor, Farhah Husna; Abdullah, Shakila; Yuniarto, Adhi; Ibrahim, Zaharah; Md Nor, Muhamad Hanif; Tony Hadibarata, Tony Hadibarata (Elsevier, 2021)
Textile dyes are recalcitrant molecules and contain a high level of chemicals and colour which poses a serious challenge to surrounding environments. Therefore, this study aims to produce biosurfactant and investigate the synergistic action on decolourisation of textile dyes by the combination of bacteria and biosurfactant. An effective dye degrading strain and biosurfactant-producer, Kurthia gibsonii KH2, was isolated from textile wastewater using molasses as the only source of carbon and energy. The isolates were identified and screened for biosurfactant production using haemolytic activity, oil spreading technique, drop collapse test and emulsification index. Fourier Transform Infrared Spectrum (FTIR) and Thin Layer Chromatography (TLC) analyses were carried out to detect the type of biosurfactant. The effect of different physicochemical parameters on textile wastewater decolourisation was assessed within 24 h. The Kurthia gibsonii KH2 showed positive results for haemolytic activity, oil spreading technique, and drop collapse test. The emulsification test (E24) revealed that Kurthia gibsonii KH2 had a higher emulsification index of 63%. FTIR and TLC analyses indicated that the biosurfactant was a lipopeptide and was formed with a yield of 2 gL−1. The synergistic activity of Kurthia gibsonii KH2 and lipopeptide biosurfactant resulted in decolourisation levels of 85% at 100 mg/L concentration and pH 7 was recorded at 168 h of incubation. The high attributes of these combinations and the phytotoxicity tests implied that the metabolites were less toxic, making it a promising option for the biodecolourisation and biodegradation of industrial textile wastewater and various environmental conditions.